Photocatalytic CO2 reduction for C2-C3 oxy-compounds on ZIF-67 derived carbon with TiO2. (April 2022) - Sung, Pei-Hsun; Huang, Chih-Yang; Lin, Chan-Yi; Chung, Po-Wen; Chang, Yu-Chung; Chen, Li-Chyong; Chen, Hsin-Yu; Liao, Chien-Neng; Chiu, Erh-Li; Wang, Cheng-Yu
Abstract: Excess carbon dioxide emission accompanied by gross fossil fuel consumption has worsened the global warming crisis in recent decades. Photo-induced conversion of CO2 into hydrocarbons is a potential solution to mitigate both energy and environmental problems. However, conventional photocatalysts suffer low efficiency in CO2 conversion with often C1 and/or C2 products. In this work, pyrolyzed cobalt type zeolitic imidazolate framework (ZIF-67), namely ZIF-derived carbon (ZDC) with residual Co nanoparticles and the corresponding ZDC/TiO2 composite (ZDC/T), were adopted as gas-phase CO2 reduction photocatalysts. The ZDC photocatalyst is inclined to form C2 compound (acetaldehyde), while the ZDC/T composite has high selectivity in C3 product (acetone). High pyrolysis temperature would degrade the photocatalytic performance in neat ZDC due to enhanced cobalt aggregation and nitrogen loss after breaking ZIF-67 Co-N coordination. Alternatively, the pyrolyzed ZDC/T revealed superior photocatalytic CO2 reduction performance because the Co-N bonds were found to decrease without changing Co nanoparticle size and dissociation of nitrogen notably. In conclusion, we synthesized novel photocatalysts for multi-carbon (C2 -C3 ) products with high selectivity, and provided a plausible mechanism to illustrate the formation process of multi-carbon products during photoreduction of CO2 . Graphical Abstract: The synergistic effect among Co nanoparticle, N-doped carbon, and black TiO2 leads to C3 product with high efficiency. ga1 Highlights: The photocatalysts of ZIF-67 derived carbon with and without TiO2 (ZDC and ZDC/T) are applied for CO2 reduction. The well-dispersed Co on N-doped carbon and black TiO2 are obtained from ZIF/TiO2 carbonization. The C2 acetaldehyde is the major product with ZDC photocatalyst. The C3 acetone is the major product with high selectivity and good quantum efficiency with ZDC/T photocatalyst. The synergistic effect between Co, N defect on carbon, and black TiO2 results in C3 product in photocatalysis.